Eco-Friendly Synthesis of Gold Nanoparticles through Gracilaria sp Seaweed Extract for Foam Height Stability in Liquid Hand Soap Formulations - Syahjoko Saputra, Iwan; Hermadi Saputro, Anjar; Adliani, Nur; Rahmi, Dwinna; Sudirman, Sudirman; Nopiandi, Yogi (The Journal of Pure and Applied Chemistry Research, 2021)
Gold nanoparticles (G-NPs) were successfully synthesized using Gracilaria sp seaweed extract. Visually, color changes from purple-blue to ruby red and then finally to pink. UV-Vis spectrophotometer showed the optimum condition of G-NPs at 531 nm wavelength with an absorbance value of 1.1. The fourier transform infrared (FTIR) spectroscopy shows the absorption peak of functional groups at the Gracilaria sp seaweed extract like hydroxyl group (-OH), aromatic (C=C), alkane (C-H), and amine (C-N) at the wavenumbers of 3356, 1613, 1456, and 1182 cm-1, respectively. The X-ray diffraction (XRD) shows the crystallinity peaks of G-NPs at 2Î¸: 38.3o, 44.1o, 64.8o, and 77.8o with miller indices of (111), (200), (220), and (311). The Particle size analyzer (PSA) shows the distribution and particle size average of G-NPs was 11.8 nm. Analysis of particle zeta charge (PZC) confirms the total charge of inter-particles was -24.7 mV. The transmission electron microscopy (TEM) images shows the G-NPs was spherical shape with a particle size was 20 nm. The hand soap@G-NPs have a pH of 6.0 and foam height stability of 4.1 cm for 10 min.